(untitled) (World Bulletin of Social Sciences, 2021)
Since ancient times, the territory of Uzbekistan has been inhabited by numerous nationalities who lived in peace and harmony, carried on a common household economy. The article describes the life of the Tajiks of the Nurata oasis, their traditions, cultural customs, economic life. Reforms of the state aimed at the socio-economic support of various nationalities, including ethnic Tajiks, through the creation of institutional institutions, the development of social infrastructures are highlighted